Download presentation
Presentation is loading. Please wait.
1
Converting Quadratic Equations
A step-by-step guide with practice
2
Intercept Form to Standard Form
Write the equation in standard form: y = – 2(x + 3)(x – 2) If you need a hint …go to next slide to see next step.
3
Intercept Form to Standard Form
Write the equation in standard form: y = – 2(x + 3)(x – 2) y = – 2(x2 + x – 6) multiply binomials If you need a hint …go to next slide to see next step.
4
Intercept Form to Standard Form
Write the equation in standard form: y = – 2(x + 3)(x – 2) y = – 2(x2 + x – 6) multiply binomials y = – 2x2 – 2x distribute
5
Intercept Form to Standard Form
Try these: y = 3(x + 1)(x + 2) y = ½ (2x + 3)(x – 2) Check your answers on the next slide.
6
Intercept Form to Standard Form
Try these: y = 3(x + 1)(x + 2) y = 3x2 + 9x + 6 y = ½ (2x + 3)(x – 2) y = x2 – ½ x – 3
7
Vertex Form to Standard Form
Write this equation in standard form: y = 2(x – 3)2 + 4 If you need a hint …go to next slide to see next step.
8
Vertex Form to Standard Form
Write this equation in standard form: y = 2(x – 3)2 + 4 y = 2(x2 – 6x + 9) + 4 square the binomial If you need a hint …go to next slide to see next step.
9
Vertex Form to Standard Form
Write this equation in standard form: y = 2(x – 3)2 + 4 y = 2(x2 – 6x + 9) + 4 square the binomial y = 2x2 – 12x distribute If you need a hint …go to next slide to see next step.
10
Vertex Form to Standard Form
Write this equation in standard form: y = 2(x – 3)2 + 4 y = 2(x2 – 6x + 9) + 4 square the binomial y = 2x2 – 12x distribute y = 2x2 – 12x combine like terms
11
Vertex Form to Standard Form
Try these: y = 3(x + 1)2 – 5 y = – (x + 3)2 – 2 Check your answers on the next slide.
12
Vertex Form to Standard Form
Try these: y = 3(x + 1)2 – 5 y = 3x2 + 6x – 2 y = – (x + 3)2 – 2 y = – x2 – 6x – 11
13
Standard Form to Intercept Form
Write the equation in intercept form: y = – 15x2 + 3x + 12 If you need a hint …go to next slide to see next step.
14
Standard Form to Intercept Form
Write the equation in intercept form: y = – 15x2 + 3x + 12 y = – 3(5x2 – x – 4) common factor If you need a hint …go to next slide to see next step.
15
Standard Form to Intercept Form
Write the equation in intercept form: y = – 15x2 + 3x + 12 y = – 3(5x2 – x – 4) common factor y = – 3(5x + 4)(x – 1) factor the trinomial
16
Standard Form to Intercept Form
Try these: y = x2 – 12x + 32 y = 5x2 – 25x + 30 Check your answers on the next slide.
17
Standard Form to Intercept Form
Try these: y = x2 – 12x + 32 y = (x – 8)(x – 4) y = 5x2 – 25x + 30 y = 5(x – 2)(x – 3)
18
Standard Form to Vertex Form
Write the equation in vertex form: y = 3x2 – 6x + 8 If you need a hint …go to next slide to see next step.
19
Standard Form to Vertex Form
Write the equation in vertex form: y = 3x2 – 6x + 8 y = 3(x2 – 2x ) + 8 factor out “a” If you need a hint …go to next slide to see next step.
20
Standard Form to Vertex Form
Write the equation in vertex form: y = 3x2 – 6x + 8 y = 3(x2 – 2x ) + 8 factor out “a” y = 3(x2 – 2x + 1) + 8 – 3 complete the square If you need a hint …go to next slide to see next step.
21
Standard Form to Vertex Form
Write the equation in vertex form: y = 3x2 – 6x + 8 y = 3(x2 – 2x ) + 8 factor out “a” y = 3(x2 – 2x + 1) + 8 – 3 complete the square y = 3(x – 1) factor and combine
22
Standard Form to Vertex Form
Try these: y = x2 – 4x + 10 y = – 2x2 – 4x + 1 Check your answers on the next slide.
23
Standard Form to Vertex Form
Try these: y = x2 – 4x + 10 y = (x – 2)2 + 6 y = – 2x2 – 4x + 1 y = – 2(x + 1)2 + 3
24
More Practice Write this equation in intercept form: y = (x + 4)2 – 1
Write this equation in vertex form: y = (x – 3)(x + 1) Check your answers on the next slide.
25
More Practice Write this equation in intercept form: y = (x + 4)2 – 1
y = (x + 5)(x + 3) Write this equation in vertex form: y = (x – 3)(x + 1) y = (x – 1)2 + 1
Similar presentations
© 2025 SlidePlayer.com Inc.
All rights reserved.